Osmosonication parameters affect Salmonella Typhimurium and Lactobacillus rhamnosus reductions in solutions and fruit juices - Bermúdez-Serrano, Ileana Maricruz (2024)
Introduction. Sonication followed by storage in high osmotic pressure, referred to as osmosonication, can significantly reduce microbial loads in food products. Understanding the parameters that influence these reductions is essential. Objective. To evaluate the effect of osmosonication parameters on the reduction of Salmonella Typhimurium and Lactobacillus rhamnosus in model solutions and fruit juices. Materials and methods. This study was conducted at the Universidad de Costa Rica, San José, Costa Rica between January and December 2012. Completely randomized experiments were designed for both model solutions and fruit juices, with data analyzed using ANOVA. The parameters evaluated included amplitude (20, 25, 30, 35, and 40 %), sonication time (10, 20, and 30 minutes), percentage of pulsations time (90, 50, 10, and 0), pectin content (0, 0.5, and 1,0 %), and cellulose content (0, 0.15, and 0.30 %), pH (2.5; 3.5; 4.5; 5.5, and 6.5) or natural juice pulp content. Results. L. rhamnosus demonstrated greater resistant to osmosonication treatments compared to S. Typhimurium. Microbial reductions increased with higher sonication times and amplitudes. The percentage of pulsations time did not significantly influence bacterial reductions. Lower pH values resulted in reduced bacterial resistance to osmosonication. Neither pectin nor cellulose content significantly affected the resistance of either microorganism to osmosonication. Similar treatments applied to fruit juices (blackberry, pineapple, apple, and coconut water) showed that microbial reductions for both bacteria were influenced by the type of juice, likely due to varying pH levels. These effects was also bacteria-dependent. Pulp content affected bacterial resistance to osmosonication, with the impact varying by bacterial species. Conclusions. Osmosonication parameters such as amplitude, time, pH, and the pulp content influence the reduction of Salmonella Typhimurium and Lactobacillus rhamnosus in model solutions and fruit juices.